Serum lipid profile as predictor of clinical outcome in pediatric patients with dengue infection at a tertiary care hospital - Siddiqui, Mohd. Saeed S.; Loya, Amruta Kailash; Kanumala, Udaykumar; Kakade, Jagannath R. (International Journal of Contemporary Pediatrics, 2019)
Background: Dengue is a serious mosquito-borne viral disease which in recent years has become a major international public health concern. Early detection of individuals at risk of developing severe forms of dengue could be possible with the identification of an ideal biomarker, which has been the focus of several research studies. Changes in lipoprotein profile during infection probably are primarily cytokine induced Interactions between microorganisms and lipoproteins occur in viral infections. There have been very few studies that address and elucidate a correlation between dengue fever severity and changes in the lipid profile. Methods: This study was conducted in paediatric patients with dengue infection of age group between 1 to 18 years MGM Medical College and Tertiary Care Hospital of Aurangabad City. Results: There was statistically significant association between TG (mg/dl) level and dengue disease category (DF vs DHS+DSS) among the patients. Overall the combine lipids were significantly predicting dengue disease category (DF, DHS and DSS). Serum lipids (triglycerides, LDL and cholesterol) among the patients significantly predict dengue disease category (DF, DHS and DSS). There was negative correlation between triglycerides level and HDL and hospital Stay which was found to be statistically significant. Conclusions: Reduced serum lipid profile can be used as a cost-effective laboratory investigation prompting a high suspicion of severe dengue infection especially in resource poor setting where serological tests may not be available.